Development of scorm compliant LMS: a comparative study among selected global standards / Nurmaisara Za'ba … [et_al.] - Za'ba, Nurmaisara; Mamat, Mohd Nor; Isa, Mohd Ali; Ramakrisnan, Prasanna; Abd Aziz, Azlan (Research Management Institute (RMI), 2009)
Online learning is known as a crucial mode of the future of educational culture. Learning Management System (LMS) is a web based application where the learners are able to log on as well as access the courses which are allocate online to them. However, most LMS will simply manage the learning contents, the learning history data, the test results, and many more without managing the learning itself. Thus, the choice of an LMS is an important part of an organization's e-learning strategy and it will affect the organization for long period of time. Sharable Content Object Reference Model (SCORM) is a standard that allows the interoperability of learning tools and course content and provides a collection of specifications adapted from multiple sources to offer a comprehensive suite of e-learning capabilities that enable interoperability, accessibility and reusability of Web-based learning content. i-Learn Portal is the LMS platform that promote information sharing and resources for the academicians and students of the University of Technology MARA (UiTM), and the portal also provides standard content for the respective courses for student's perusal, extending the discussion or lecture at a class. The i-Learn Centre (i-LeC) of UiTM realizes that there is a need to standardize the i-Learn Portal towards world recognized LMS and therefore this research is done to understand SCORM and a comparative study among other selected global standards such as IEEE LTSC and IMS Global Consortium is carried out.